Clarification of the Taxonomic Position of Auxemma, Patagonula, and Saccellium (Cordiaceae, Boraginales) - Gottschling, M; Miller, J.S.
Auxemma, Patagonula, and Saccellium (Cordiaceae, Boraginales)were all described as distinct from Cordia because of highly specialized fruit morphologies, and subsequent authors have almost universally continued to maintain them. However, both molecular and morphological data indicate that they are nested within Cordia, and the nomenclatural changes necessary to accommodate them in Cordia are proposed here. Complete synonomy, a key to all species formerly belonging to Auxemma, Patagonula, and Saccellium, and notes on their distributions as inferred from modern collections are provided.
Keywords: BORAGINACEAE; CORDIA; CORDIOIDEAE; FRUIT MORPHOLOGY; SOUTH AMERICA; TAXONOMY